2012
DOI: 10.1016/j.cellimm.2011.11.010
|View full text |Cite
|
Sign up to set email alerts
|

PPAR-γ agonists, mainly 15d-PGJ2, reduce eosinophil recruitment following allergen challenge

Abstract: We evaluate the immunomodulation of Peroxisome proliferator-activated receptor-γ (PPAR-γ) agonists 15d-PGJ(2) and rosiglitazone (RGZ) in a model of chronic eosinophilia. 15d-PGJ(2) and RGZ significantly reduce eosinophil migration into the peritoneal cavity and down-regulate the eosinopoiesis. The synthesis of IL-5 was decreased after the treatment with 15d-PGJ(2) and RGZ corroborating with the eosinophil migration inhibition. However, IgE was decreased only after the administration of 15d-PGJ(2) in part due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 38 publications
0
24
0
3
Order By: Relevance
“…The ω-3-derived resolvins, protectins, and maresins also display potent proresolving actions in a variety of cell types and in in vivo models of inflammatory diseases, including asthma, acute lung injury, and cystic fibrosis (147151). Moreover, 15d-PGJ 2 resolves chronic eosinophilia following allergen challenge, decreasing airway inflammation (152). Similarly, 15d-PGJ 2 treatment of carrageenan-induced acute lung injury reduces BAL leukocyte and albumin levels in an Nrf2-dependent manner (153).…”
Section: Physiological and Therapeutic Implicationsmentioning
confidence: 99%
“…The ω-3-derived resolvins, protectins, and maresins also display potent proresolving actions in a variety of cell types and in in vivo models of inflammatory diseases, including asthma, acute lung injury, and cystic fibrosis (147151). Moreover, 15d-PGJ 2 resolves chronic eosinophilia following allergen challenge, decreasing airway inflammation (152). Similarly, 15d-PGJ 2 treatment of carrageenan-induced acute lung injury reduces BAL leukocyte and albumin levels in an Nrf2-dependent manner (153).…”
Section: Physiological and Therapeutic Implicationsmentioning
confidence: 99%
“…Recently, our and other research groups have demonstrated the anti-inflammatory activity of exogenously administered 15d-PGJ 2 (12)(13)(14)(15)(16)(17)(18). However, it has been estimated that .50% of the 15d-PGJ 2 added exogenously to a biological system binds to albumin (11).…”
Section: {‖mentioning
confidence: 99%
“…(A) Mice were sensitized by intraperitoneal injection of ovalbumin [28] mixed with aluminum hydroxide on days 0, 7, and 14. Daily OVA intranasal challenge was performed from days 21 to 27.…”
Section: Methodsmentioning
confidence: 99%